Una aproximación a verbos de lanzamiento como auxiliares de perífrasis incoativas: los casos de echar(se) + INF, lanzarse + INF y aventarse + INF en el español mexicano - Castellanos Armenta, Julieta (2025)
This paper reviews the factors that determine the added semantic value of inchoative periphrasis with a throwing verb as an auxiliary. It is acknowledged that the basic semantics of the auxiliary verb is conclusive in the interpretation of the event as having an unexpected beginning, as it has traditionally been proposed for the periphrastic construction echarse a + infinitive. Based on a qualitative analysis of echar a + infinitive, echarse a + infinitive, lanzarse a + infinitive and aventarse a + infinitive, using data from Mexican written registers, it is determined that the motivations behind the specific inchoative nuance in these constructions are associated with morphosyntactic parameters, the lexical aspect of infinitives, the semantic role of the subject and sentential contexts.